Nanocrystalline ceria coatings on solid oxide fuel cell anodes: the role of organic surfactant pretreatments on coating microstructures and sulfur tolerance - Wu, Chieh-Chun; Tang, Ling; De Guire, Mark R. (Beilstein Journal of Nanotechnology, 2014)
Treatments with organic surfactants, followed by the deposition of nanocrystalline ceria coatings from aqueous solution, were applied to anodes of solid oxide fuel cells. The cells were then operated in hydrogen/nitrogen fuel streams with H2S contents ranging from 0 to 500 ppm. Two surfactant treatments were studied: immersion in dodecanethiol, and a multi-step conversion of a siloxy-anchored alkyl bromide to a sulfonate functionality. The ceria coatings deposited after the thiol pretreatment, and on anodes with no pretreatment, were continuous and uniform, with thicknesses of 60–170 nm and 100–140 nm, respectively, and those cells exhibited better lifetime performance and sulfur tolerance compared to cells with untreated anodes and anodes with ceria coatings deposited after the sulfonate pretreatment. Possible explanations for the effects of the treatments on the structure of the coatings, and for the effects of the coatings on the performance of the cells, are discussed.
Keywords: cerium(IV) oxide; microstructure; organic self-assembled monolayers; solid oxide fuel cells; sulfur tolerance